Calibration of pelagic stereo‐BRUVs and scientific longline surveys for sampling sharks. Issue 8 (12th July 2014) - Santana‐Garcon, Julia; Braccini, Matias; Langlois, Tim J.; Newman, Stephen J.; McAuley, Rory B.; Harvey, Euan S.; Freckleton, Robert
Summary Our understanding of the ecology of sharks and other highly mobile marine species often relies on fishery‐dependent data or extractive fishery‐independent techniques that can result in catchability and size‐selectivity biases. Pelagic Baited Remote Underwater stereo‐Video Systems (pelagic stereo‐BRUVs) provide a standardized, non‐destructive and fishery‐independent approach to estimate biodiversity measures of fish assemblages in the water column. However, the performance of this novel method has not yet been assessed relative to other standard sampling techniques. We compared the catch composition, relative abundance and length distribution of fish assemblages sampled using pelagic stereo‐BRUVs and conventional scientific longline surveys. In particular, we focused on sharks of the family Carcharhinidae (requiem sharks) to assess the sampling effectiveness of this novel technique along a latitudinal gradient off the coast of Western Australia. We calibrated the sampling effort required for each technique to obtain equivalent samples of the target species and discuss the advantages, limitations and potential use of these methods to study highly mobile species. The proportion of sharks sampled by pelagic stereo‐BRUVs and scientific longline surveys was comparable across the latitudinal gradient. Carcharhinus plumbeus was the most abundant species sampled by both the techniques. Longline surveys selected larger individuals of the family Carcharhinidae in comparison with the length distribution data obtained from pelagic stereo‐BRUVs. However, the relative abundance estimates (catch per unit of effort) from the pelagic stereo‐BRUVs were comparable to those from 5 to 30 longline hooks. Pelagic stereo‐BRUVs can be calibrated to standard techniques in order to study the species composition, behaviour, relative abundance and size distribution of highly mobile fish assemblages at broad spatial and temporal scales. This technique offers a non‐destructive fishery‐independent approach that can be implemented in areas that may be closed to fishing and is suitable for studies on rare or threatened species.